2005
DOI: 10.1177/0018726705057173
|View full text |Cite
|
Sign up to set email alerts
|

Women’s appeals for equity at American universities

Abstract: Statistics indicate that sex discrimination is still very evident at American universities. To explore whether inadequate university responses when individuals complain of inequities may be a factor, a qualitative study was conducted using individual interviews with 14 students and faculty who experienced sex discrimination. Results indicated the women first made attempts to address their situations informally and were hopeful that changes would result. Although changes sometimes occurred, responses to these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Further, the behaviour of some male guests is particularly problematic as the requirement for attendants to be submissive and subservient to guests makes it difficult for them to be proactive in deterring harassment (Bedford and Hwang, ). Also, it is believed that organizational tolerance may play a significant role in the incidence of sexual harassment by a lack of, or ineffective, policies and procedures (Goltz, ). Most room attendants felt that their establishment had ineffective measures to deal with sexual harassment.…”
Section: Hotel Workplace Culturementioning
confidence: 99%
“…Further, the behaviour of some male guests is particularly problematic as the requirement for attendants to be submissive and subservient to guests makes it difficult for them to be proactive in deterring harassment (Bedford and Hwang, ). Also, it is believed that organizational tolerance may play a significant role in the incidence of sexual harassment by a lack of, or ineffective, policies and procedures (Goltz, ). Most room attendants felt that their establishment had ineffective measures to deal with sexual harassment.…”
Section: Hotel Workplace Culturementioning
confidence: 99%
“…Preconceived notions that some careers are gender specific can account for some of the discrimination of STEM women (Goltz, 2005). Discrimination often manifests in subtle, covert ways (NRC, 2007).…”
Section: Departmental Climate: Discrimination and Sexismmentioning
confidence: 99%
“…For example, women are assigned heavier teaching and service responsibilities (Bailyn, 2003), are interrupted more, and are marginalized in meetings (Schmaling, 2007). Many women do not report discrimination because they do not expect their reports to be taken seriously, they expect to experience backlash or retaliation, and they perceive procedures for dealing with discrimination are lacking or ineffective (Goltz, 2005). Furthermore, women working in a department with a history of gender bias report less job satisfaction and more discrimination compared to national averages (Greene et al, 2010).…”
Section: Departmental Climate: Discrimination and Sexismmentioning
confidence: 99%
“…Nonetheless, the findings challenged the general public perception that men were not as concerned as women about their family roles and relationship needs. Additionally, the results revealed that these men tended not to see their experiences in academia as related to their sex, implying that the academy treated both men and women the same, which according to women in academia is far from reality (Goltz, 2005).…”
Section: Discussionmentioning
confidence: 89%